Cooperative shear in bulk metallic glass composites containing metastable β-Ti dendrites - Zhang, L. (2021)
We report a novel plastic deformation mechanism of bulk metallic glass composites (BMGCs) containing metastable β−Ti dendrites. Plastic deformation of the BMGCs beyond the ultimate tensile strength is mediated by cooperative shear events, which comprise a shear band in the glassy matrix and a continuous ω−Ti band with a thickness of ∼10  nm in the β−Ti dendrite. The cooperative shear leads to serrated shear avalanches. The formation of narrow ω−Ti bands is caused by high local strain rates during the cooperative shear. The cooperative shear mechanism enriches the deformation mechanisms of BMGCs and also deepens the understanding of ω−Ti formation.